Modifikasi Excavator Menggunakan Tabung Penyimpan Udara Bertekanan (Pressure Vessel) Sebagai Media Edukasi - Supriadi Supriadi; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Excavators are heavy equipment used to move material from one place to another.Excavators are widely used in various fields, namely: construction, mining,infrastructure, etc.The University of Riau has produced a mini excavator model design in the Hydraulic and Pneumatic Laboratory of the Faculty of Engineering Mechanical Engineering using a pneumatic system based on undercarriage, equipped with a remote control system, and 360˚ swing rotation.This research was modified the air supply section , in the design of the tube using a two data that the calculation and software autodesk inventor 2015, This research was revealed the highest strees calculation data results of head 9.05 MPa and shell of 4.56 MPa, while data software autodesk inventor 2015 that was obtained the highest strees head of 4.15 MPa and shell of 4.49 MPa.The tube pressure of 5.8 bars of total air requirement wason a pneumatic system of 3.8 bars and the remaining air that was stored in 2 bars. The pneumatic system can drive the air pressure of 5.8-6 bars. Therefore, the movement was likelyan excavator in general.Key Word : excavator, presurre, strees analysis